2013
DOI: 10.4209/aaqr.2013.03.0070
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of NOx, SOx and CO2 Emissions of Taiwan’s Thermal Power Plants by Data Envelopment Analysis

Abstract: An integrated environmental and operational evaluation model is constructed by data envelopment analysis (DEA) to examine seven thermal power plants operating in Taiwan during [2001][2002][2003][2004][2005][2006][2007][2008]. Inputs and desirable outputs along with undesirable outputs, including CO 2 , SO x , and NO x emissions, were simulated. A slack variable analysis was conducted to identify possible ways to improve the inefficient power plants. In addition, three models were compared to identify the actua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The flue gases of thermal power plants in Taiwan have shown high CO 2 , NOx, and SOx emissions [27]. The current study showed that the high concentrations of CO 2 , NO and SO 2 present in the flue gases had negative effects on the growth and CO 2 sequestration processes of C. vulgaris ESP-31 wild type (net photosynthetic O 2 evolution rate).…”
Section: Discussionmentioning
confidence: 67%
“…The flue gases of thermal power plants in Taiwan have shown high CO 2 , NOx, and SOx emissions [27]. The current study showed that the high concentrations of CO 2 , NO and SO 2 present in the flue gases had negative effects on the growth and CO 2 sequestration processes of C. vulgaris ESP-31 wild type (net photosynthetic O 2 evolution rate).…”
Section: Discussionmentioning
confidence: 67%
“…The emissions from power generation not only affect Local air quality but also transport over long distance and cause regional/global environmental issues (Huang et al, 2016). Studies related to emission measurement and estimations from thermal power plants conducted by different researchers (Mittal and Sharma, 2003b;Gurjar et al, 2004;Blottnitz, 2006;Nazari et al, 2010, Tsilingiridis et al, 2011Liu et al, 2013, Huang et al, 2016 have confirmed the pollution potential of the measured gases particularly with respect to the increasing trend in temperature or in other words global warming and therein lies the importance of carrying out this project work to determine the amount of emissions of these gases particularly for a very fast developing economy like.…”
Section: 5total Greenhouse Gases Emissionmentioning
confidence: 99%
“…Many studies have used dynamic data envelopment analysis (DEA) models to analyze the energy and environmental efficiencies in different countries (Zofio and Prieto 2001;Ramanathan 2005;Kumar 2006; Gomes and Lins 2007;Zhou, Poh, and Ang 2007;Li and Wang 2014;Liu and Wang 2014;Robaina-Alves, Moutinho, and Macedo 2015;Gómez-Calvet et al 2016) and different enterprises. For example, Pacudan and de Guzman (2002) evaluated the energy efficiency of 15 power companies in the Philippines, Vaninsky (2008) examined the environmental efficiency of U.S. power companies during 1990-2006, Lin, Liu, and Lewis (2012) assessed the CO 2 emissions impact of the electricity sector, and Liu, Lin, and Lewis (2013) evaluated the NO X , SO X , and CO 2 emissions in Taiwan's thermal power plants.…”
Section: Introductionmentioning
confidence: 99%